Human Resource Management and Artistic Enterprise: Evolving the Business Paradigm in Contemporary Painting Space - Kafaru, Abiodun Babatunde; Adedayo, Adeyemi; Ogunowo, Taiye; Savage, Olusegun (NIU Journal of Humanities, 2025)
Artists and art managers are very relevant in the chain of artistic production and distribution. However, the trend in contemporary Nigeria art landscape is different, whilst the artist is solely responsible in an unfair process of managing production, marketing, and the distribution of his/her artistic product. Therefore, the role of art manager is much needed human resource that could and should – shoulder the extracurricular responsibilities in marketing art for profit. Unfortunately, up until now, insignificant efforts have been made by artists, art promoters, art scholars, curriculum planners and the Nigeria government in putting in place appropriate framework to actually help or give artists and artworks the value they deserve. Yet corporate bodies like the Nigeria government and European aesthetic sojourners have persistently used the arts and crafts for positive global reference and promotion of Nigeria’s cultural image. Therefore, this paper is set out to examine the roles that art managers play at the core art profession, the art product industry, and its potency in the value chain of artistic distribution for maximum profit and benefit to the artist. The paper states that optimum art management, if properly channeled and well applied, will reduce stress, create standardization, thus casting positive developmental effect on the nations’ economy, innovation, and boost profit. The paper concludes that the role of arts, artists and the art managers are creatively intertwined in art development for holistic personal, national, and international progress.      Keywords: Arts, Art Managers, Human Resource Management (HRM), and Painting